New pathogenic variant in DLX5: New clues for a clinical spectrum from split-hand-foot malformation to fibular aplasia, tibial campomelia and oligosyndactyly - Sifre-Ruiz, Anna; Sagasta, Amaia; Santos, Erika; Perez de Nanclares, Guiomar; Heath, Karen E. (Frontiers in Genetics, 2023)
Introduction: FATCO (Fibular Aplasia, Tibial Campomelia and Oligosyndactyly) is a very infrequent skeletal dysplasia classified within the limb hypoplasia-reduction defects group whose genetic cause has not yet been identified. The advent of next generation sequencing is enabling the diagnosis of diseases with no previously known genetic cause. Methods: We performed a thorough autopsy on a fetus whose pregnancy was legally terminated due to severe malformations detected by ultrasound. A trio exome was run to identify the genetic cause and risk of recurrence. Previous literature of similar cases was systematically searched. Results: Anatomopathological analyses revealed complete fibular aplasia, shortened and campomelic tibia, absent ankle joint, club right foot and a split foot malformation, leading to the diagnosis of FATCO. Exome sequencing showed that the female fetus carried a de novo nonsense variant in DLX5. The literature search permitted the collection of information on 41 patients with FATCO, the majority of whom were males diagnosed postnatally. In most cases, lower limbs were affected exclusively, but in 34% of cases the upper limbs were also affected. Conclusion: The pathologies associated with DLX5 variants encompass a wide spectrum of manifestations ranging from abnormalities exclusively in the hands and feet to long bones such as the tibia and fibula.